Vittorio Alfieri e i «Quattro Poeti» - Di Benedetto, Arnaldo (Cuadernos de Filología Italiana, 2006)
During the most part of the XIXth. century the «four poets» canon was expanded, not only in Italy. Dante, Petrarca, Ariosto and Tasso were considered the highest point of italian poetry. In many editions of their masterpieces, Divina Commedia, Canzoniere, Orlando Furioso and Gerusalemme Liberata, were published together. One of those editions was prepared by the German Adolf Wagner, uncle of great compositor Richard. It is not clear when (and by whom) the canon has been established. Without any doubt one of its firts advocates and propagators was Vittorio Alfieri whose aspiration was to be included as the «number five» of «the four poets”. This article mentions all these questions and refers even to figurative reflections of the canon in some nineteenth century theatre’s front. In the front of a Lombardy noble palazzo the Alfieri’s wish seems to come true, because his image appears near those of Dante, Petrarca, Ariosto and Tasso.